Minat Memesan Kembali Jasa Transportasi Online - Iristian, Jovi - (Jurnal Ilmu Manajemen Advantage, 2019)
The number of smartphone users that continues to increase over time seems to be in line with the increasing number of users of online transportation services from the web and applications. Technology that is built by understanding the experience of its users has changed people's behavior in traveling and carrying out daily activities. The vehicle booking application in particular has been a breakthrough because it allows a convenient pick-up and delivery system at an affordable price. The purpose of this study was to determine brand experience, emotional connection to the brand and brand image to interest in ordering back online transportation services. The population is customers who use the online transportation service "Grab". This study uses 150 samples of respondents with the criteria of using online transportation services more than twice. Then the data were analyzed_using multiple regression_analysis which was channeled through the SPSS 21 program. Based on the_results of the study, the results that brand experience and emotional connection to the brand have a significant effect on the interest in ordering Grab's online transportation services, while the brand image has no significant effect on the interest in ordering Grab's online transportation services. With the variable brand experience, emotional linkages to the brand and brand image to interest in re-ordering Grab online transportation services in Surabaya amounted to 41.5% and the rest explained by other factors not explained in the regression model obtained.